(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2016)
Leukodystrophy cases are not common in routine clinical practice. Among leukodystrophies adrenoleukodystrophy (ALD) cases are more common. It presents with neurologic and endocrine features with characteristic Megnetic Resonance Image (MRI) findings and biochemical changes. Early recognition of index case is important because dietary modification & supplementation with Lorenzo’s oil can slow progression of the disease course and can be life saving. Bone Marrow Transplantation (BMT) if performed in earlier stage of disease can be very rewarding to show stabilization and in some instances improvement of patient’s condition. More over prenatal diagnosis of affected boys can be performed by analyzing pedigree chart of an affected family members of this X-linked chromosomal disease. JCMCTA 2016 ; 27 (1) : 68 - 71